Armadillidin H, a Glycine-Rich Peptide from the Terrestrial Crustacean Armadillidium vulgare, Displays an Unexpected Wide Antimicrobial Spectrum with Membranolytic Activity - Verdon, Julien; Coutos-Thevenot, Pierre; Rodier, Marie-Helene; Landon, Celine; Depayras, Segolene; Noel, Cyril; La Camera, Sylvain; Moumen, Bouziane; Greve, Pierre; Bouchon, Didier; Berjeaud, Jean-Marc; Braquart-Varnier, Christine (Frontiers in Microbiology, 2016)
Antimicrobial peptides (AMPs) are key components of innate immunity and are widespread in nature, from bacteria to vertebrate animals. In crustaceans, there are currently 15 distinct AMP families published so far in the literature, mainly isolated from members of the Decapoda order. Up to now, armadillidin is the sole non-decapod AMP isolated from the haemocytes of Armadillidium vulgare, a crustacean isopod. Its first description demonstrated that armadillidin is a linear glycine-rich (47%) cationic peptide with an antimicrobial activity directed towards Bacillus megaterium. In the present work, we report identification of armadillidin Q, a variant of armadillidin H (earlier known as armadillidin), from crude haemocyte extracts of A. vulgare using LC-MS approach. We demonstrated that both armadillidins displayed broad spectrum antimicrobial activity against several Gram-positive and Gram negative bacteria, fungi, but were totally inactive against yeasts. Membrane permeabilization assays, only performed with armadillidin H, showed that the peptide is membrane active against bacterial and fungal strains leading to deep changes in cell morphology. This damaging activity visualized by electronic microscopy correlates with a rapid decrease of cell viability leading to highly blebbed cells. In contrast, armadillidin H does not reveal cytotoxicity towards human erythrocytes. Furthermore, no secondary structure could be defined in this study (by CD and NMR) even in a membrane mimicking environment. Therefore, armadillidins represent interesting candidates to gain insight into the biology of glycine-rich AMPs.